Employee Work Motivation at the Pasangkayu Regency Education, Youth and Sports Office - Sahdiah Sahdiah; Nuraisyah Nuraisyah; Dandan Haryono; Nasrullah Nasrullah; Sajjad Hussain (PT. Multidisciplinary Press Indonesia, 2024)
This research is to determine the work motivation of employees at the Pasangkayu Regency Education, Youth and Sports Office. The type of research used is descriptive qualitative. Data types use primary data and secondary data. The theory used, McClelland's Work Motivation theory, consists of the need for achievement, the need for power and the need for affiliation. Data collection techniques are carried out through observation, interviews, and documentation. The informant withdrawal technique uses purpose. The data analysis used is the Miles, Huberman, and Saldana model, namely data collection, data presentation, data condensation and drawing conclusions. Based on the results of research conducted related to employee work motivation at the Pasangkayu Regency Education, Youth and Sports Service, the researcher concluded that employee work motivation in the aspect of the need for achievement has relatively not been implemented, because there are still many undisciplined employees who deliberately arrive late and leave quickly before time, thus affecting his work. Apart from that, the provision of rewards and sanctions is relatively inconsistent. Another factor that causes low employee achievement motivation is inadequate facilities because they have been used for a long time which makes employees less enthusiastic about working. In the aspect of the need for power, researchers see that cooperation between employees is still relatively uncooperative because employee participation is still low. Apart from that, employee career development tends to be selective, because it is still dominated by political elements. In the aspect of affiliation needs, researchers see that the communication carried out by employees is relatively good. This can be proven that when there are activities in the office, employees can work together and build collaboration between employees even though they are in different fields.